MYZOBDELLA PLATENSIS (HIRUNDINIDA: PISCICOLIDAE) IS TRUE PARASITE of BLUE CRABS (CRUSTACEA: PORTUNIDAE) - Zara, Fernando Jose [UNESP]; Diogo Reigada, Alvaro Luiz [UNESP]; Domingues Passero, Luiz Felipe [UNESP]; Toyama, Marcos Hikari [UNESP] (Amer Soc Parasitologists, 2009)
Leeches exhibit a marked scope of diversity, including different kinds of symbiosis. The aim of the present study was to demonstrate through biochemical and histological analysis that a species of piscicolid leech, Myzobdella platensis, is a true parasite of blue crabs, feeding on their hemolymph and using them as a site for cocoon deposition. In a total of 48 blue crabs collected on October 2007 at 3 sites of the Sao Vicente Estuary, 12 specimens were infested with leeches. Callinectes bocourti (n = 7) was the most infested species with leeches and cocoons; it was chosen for biochemical and histological assays. The immunoblotting assays showed a positive reaction of the proteins in the intestinal samples of leeches collected from crabs using antihemocyanin polyclonal antibody of Ampullaria canaliculata. In addition. leech intestinal samples were recognized by antihemolymph polyclonal antibody of nonparasitized blue crabs. Histological sections of leech gut showed hemocytes and a granular matrix similar to those found in crab blood vessels. Collectively, this evidence strongly suggests a parasitic interaction between the leech M. platensis and the blue crab C. bocourti, in which the former utilizes the latter as a site for cocoon deposition and possibly for dispersal similar to that proposed for Myzobdella lugubris in Callinectes sapidus in North America.